2006
DOI: 10.1111/j.1537-2995.2007.01066.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti–hepatits B core antigen testing, viral markers, and occult hepatitis B virus infection in Pakistani blood donors: implications for transfusion practice

Abstract: The study shows that more than 17 percent of healthy, young blood donors in Pakistan are already exposed to HBV, with two-thirds showing anti-HBs levels of greater than 100 mIU per mL. One in 200 blood donors who are HBsAg-, anti-HBc-positive, however, have occult HBV infection, with likelihood of transmission of hepatitis B in recipients of blood components derived from them. HBsAg-negative individuals who are anti-HBc-negative and those who are anti-HBc-positive, anti-HBs-positive, and HBV DNA-negative shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
59
5
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 14 publications
(16 reference statements)
6
59
5
6
Order By: Relevance
“…In Pakistan it is 17.3%. 10 In Spain, it is 4.8% among >65 years of donors. In literature, it is found that the isolated prevalence of anti-HBc is supposed to be 4-50% depending on sensitivity of reagent, age of donor.…”
Section: Discussionmentioning
confidence: 99%
“…In Pakistan it is 17.3%. 10 In Spain, it is 4.8% among >65 years of donors. In literature, it is found that the isolated prevalence of anti-HBc is supposed to be 4-50% depending on sensitivity of reagent, age of donor.…”
Section: Discussionmentioning
confidence: 99%
“…At least, the limitations of HBsAg checking in the context of safe blood transfusion are mostly known to many countries. [5][6][7][8][9] Unfortunately, there has been no study about the HBV infection status of HBsAgnegative blood in Bangladesh. The physicians, hepatologists, academicians and policy makers are equally unaware of the seriousness, loop holes and magnitudes of ongoing blood transfusion program of this country.…”
Section: Anti-hbc Screening Of Blood Donors In Bangladesh: Relevance mentioning
confidence: 99%
“…7 Studies from Lebanon and Pakistan have revealed HBV DNA among 2.8% and 2.9% HBsAgnegative, anti-HBc-positive blood donors, respectively. 8,9 Based on these observations, policy makers and professional organizations of these countries have been trying to optimize their blood transfusion system. However, these scientific developments have not influenced the ongoing blood transfusion program of Bangladesh, even though high prevalence of anti-HBc (22.6%) has been reported among healthy subjects of Bangladesh.…”
mentioning
confidence: 99%
“…La seguridad de los componentes sanguíneos depende de múltiples factores, entre ellos, los criterios de selección de donantes, las pruebas serológicas utilizadas para tamizar agentes infecciosos, y demás estrategias o filtros que se establezcan con el fin de disminuir la probabilidad de que individuos con riesgo de infección o unidades de sangre con estándares de calidad inadecuados, lleguen a ser transfundidos (11). Entre estos filtros, las pruebas de tamización con sensibilidad adecuada juegan un papel muy importante en la reducción de la transmisión de agentes patógenos (11 y, para otros agentes como el virus de la hepatitis C y el VIH, oscila entre 90 y 100 %, y estos virus se consideran los principales agentes de infecciones transmitidas por transfusiones (12).…”
unclassified
“…Entre estos filtros, las pruebas de tamización con sensibilidad adecuada juegan un papel muy importante en la reducción de la transmisión de agentes patógenos (11 y, para otros agentes como el virus de la hepatitis C y el VIH, oscila entre 90 y 100 %, y estos virus se consideran los principales agentes de infecciones transmitidas por transfusiones (12).…”
unclassified